Chemical synthesis, characterization and spark plasma sintering of Cu and Cu/TiO2 composite powders - Alipour Mohammad; Ardestani Mohammad; Moazami-Goudarzi Mohammad (Science of Sintering)
Pure Cu and Cu/TiO2 composite powders with 10 and 20 wt% TiO2 were synthesized via chemical precipitation method. The initial precipitates were obtained by adding ammonium hydrogen carbonate to copper nitrate and copper nitrate/TiO2 comtaining solutions drop by drop. The precipitates were calcined at 450ºC according to simultaneous thermal analysis results in air. The calcined powders were reduced in hydrogen atmosphere at 500ºC. The reduced powders were spark plasma sintered at 730ºC. The microstructural evaluations of the sintered samples showed a nearly dense microstructure with a fine dispersion of TiO2 within the Copper matrix. The hardness value of the Cu/TiO2 composites was 90 HV higher than that of pure copper. The wear test results showed that by increasing the TiO2 content, the average coefficient of friction (COF) increased so that the lowest COF was obtained for the monolithic Cu sample. However, the wear rate of Cu/10wt% TiO2 composites was the lowest among the sintered powders which was due to the highest hardness of this group of samples.